ISLAMIC PARENTING PERSPEKTIF IMAM AL-GHAZALI - Mighfar, Shokhibul (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
This article discusses parenting from the perspective of Al Ghazali, a prominent Muslim scholar. The purpose of this article is to explain the principles emphasized by Al Ghazali in raising children wisely and based on Islamic values. Al Ghazali views the importance of raising children with compassion, wisdom, and religious values. Al Ghazali stressed that children are a gift and a mandate from Allah SWT which must be respected and taken care of properly. One of the principles emphasized is the importance of instilling religious and moral values in children from an early age, including ethics and noble character. In addition, Al Ghazali emphasized the importance of being exemplary in upbringing. Parents must set a good example for their children by showing behavior that is in accordance with religious values and morality. Children tend to imitate what they see from their parents, therefore it is the responsibility of parents to set a good role model in all aspects of life. Good communication between parents and children is also very important. Parents should listen attentively and empathetically and provide needed support and guidance. Good listening helps understand children's feelings and needs and gives them a sense of security and understanding. This article also underscores the importance of avoiding emotional neglect of children. Parents must provide attention, affection, and acknowledgment of their children's feelings and needs. They must be sensitive to children's emotions, provide the necessary emotional support and help them manage their emotions wisely. Ghazali's parenting approach emphasizes the importance of providing holistic education to children. Al Ghazali's perspective on parenting emphasizes the importance of raising children with love, example, good communication, and holistic education. These principles help form children who have noble and quality morals. This article provides valuable insights for parents in carrying out their duties in raising children according to Al Ghazali's perspective.